2022
DOI: 10.3389/fnagi.2022.925728
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hippocampal neurogenesis mediated by PGC-1α-activated OXPHOS after neonatal low-dose Propofol exposure

Abstract: BackgroundDeveloping brain is highly plastic and can be easily affected. Growing pediatric usage of anesthetics during painless procedures has raised concerns about the effect of low-dose anesthetics on neurodevelopment. It is urgent to ascertain the neuronal effect of low-dose Propofol, a widely used anesthetic in pediatrics, on developing brains.MethodsThe behavioral tests after neonatal exposure to low-dose/high-dose Propofol in mice were conducted to clarify the cognitive effect. The nascent cells undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…These pathways play an important role in the autocrine and paracrine functions of the cell membrane and cell proliferation activities (15,16). Chen et al concluded that low-dose (10 µM) propofol activated hippocampal neurogenesis, increased the number of viable cells and expressed higher mitochondrial metabolism genes in cultured neural stem cells, while highdose (100 µM) propofol did not affect these cells (17). However, Lv et al indicated that 5 and 25 µM propofol inhibited lipopolysaccharide-induced apoptosis in lung epithelial cell cultures, while 1 µM propofol had no effect (18).…”
Section: Resultsmentioning
confidence: 99%
“…These pathways play an important role in the autocrine and paracrine functions of the cell membrane and cell proliferation activities (15,16). Chen et al concluded that low-dose (10 µM) propofol activated hippocampal neurogenesis, increased the number of viable cells and expressed higher mitochondrial metabolism genes in cultured neural stem cells, while highdose (100 µM) propofol did not affect these cells (17). However, Lv et al indicated that 5 and 25 µM propofol inhibited lipopolysaccharide-induced apoptosis in lung epithelial cell cultures, while 1 µM propofol had no effect (18).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of tissue repair in the developing brain by enhancing the proliferative potential of the neurogenic niches is currently under active investigation [ 26 , 27 , 28 ]. The modulation of the ECS to activate the neurogenic response after adult ischemia has been postulated [ 29 , 30 ], so we wondered if the administration of the endocannabinoid 2-AG could generate a neuroprotective and/or neuroregenerative response after neonatal HI.…”
Section: Discussionmentioning
confidence: 99%